PreScribed (A Life Written for Me): A Theatrical Qualitative Research-Based Performance Script Informed by General Practitioners' Experiences of Emotional Distress. (19th April 2021) - Riley, Ruth; Spiers, Johanna; Gordon, Viv
This paper includes the script from a research-informed, theater-based production titled PreScribed (A Life Written for Me), which depicts the life of a distressed General Practitioner (GP) who is on the verge of breaking down and burning out. The authors provide context for the collaboration between artist and researchers and report on the creative methodological process involved in the co-production of the script, where research findings were imaginatively transformed into live theater. The researchers provide their reflections on the process and value of artistic collaboration and use of theater to disseminate research findings about emotions to wider audiences. It is concluded that qualitative researchers and artists can collaborate to co-create resonant and powerful pieces of work which communicate the emotions and experiences of research participants in ways that traditional academic dissemination methods cannot. The authors hope that sharing their experiences and this script as well as their reflections on the benefits of this approach may encourage researchers and artists to engage in this type of methodological collaboration in the future.